Civil Resistance - Randle Michael (Fontana Press, 1994)
A broad and detailed examination of both the history and philosophy of civil resistance, including its possible future role as an alternative, or complement, to military defence in resisting coups and foreign occupation. Introduction, Civil Resistance and Realpolitik, The Evolution of Passive Resistance, Satyagraha to People Power, The Dynamics of Non-Violent Action, An Alternative Defence? The Birth of a Concept, The Strategy of Civilian Resistance, Popular Empowerment and Democratic Values, Civil Resistance in the 1990s, Appendix, Reference Notes, Index.